Liver-directed gene therapy - Brunetti-Pierri, Nicola (Henry Stewart Talks, 2022)
Liver metabolism, Gene therapy strategies, Inborn errors of metabolism, Biochemical genetics, Viral vectors for gene therapy in the liver, In vivo gene therapy, Viral vectors and genotoxicity, Non-viral vectors